Evaluating the Success of Watershed Rehabilitation Efforts in Gowa Regency: A Case Study on Forest and Land Restoration - Mukti, Jauhar; hikmah, Hikmah; Kurniawan, Hendra; Sabri, Ahmad; Arty, Budi; Semu, Yuslan Demma (Jurnal Wasian, 2023)
The Ministry of Environment and Forestry designates forest and land rehabilitation (RHL) initiatives as a top priority in national policies. Forest and land rehabilitation refers to the deliberate actions taken to restore, preserve, and enhance the functionality of forests and land. Therefore, this study is to assess the viability of cultivating RHL plants. The methodology employed is the observation approach, which entails gathering data firsthand at the specific site. Plant area measurements are conducted on the physical planting area, quantified in hectares, and then compared to the intended plant area as specified in the design. Plant evaluation and assessment is conducted using the Systematic Sampling with Random Start approach, which involves randomly selecting the first measurement plot and then systematically selecting successive measuring plots. The sampling utilised a 5% interval. Rectangular measurement plots are formed with dimensions of 40 meters by 25 meters, resulting in an area of 0.1 hectares. The number of measuring plots can be determined by multiplying the percentage of interest (5%) by the plot area (in hectares) and then dividing by the area of each measuring plot (in hectares). This calculation results in a total of 43 measuring plots. The research findings indicate that the success rate of plant development varies between 76.33% and 77.17%, with an average value of 76.62%.